Public Health and Education Spending in Ghana in 1992-98 : Issues of Equity and Efficiency - Canagarajah, Sudharshan; Ye, Xiao (World Bank, Washington, DC, 2014)
Using primary data from the health and education ministries, and household survey data from the Ghana Statistical Service, the authors analyze equity, and efficiency issues in public spending on health, and education in Ghana in the 1990s. Public expenditures in the education sector, declined in the second half of the 1990s. Basic education enrollment has been stagnant, or declining in public schools, but increasing in private schools, resulting in a moderate increase in total enrollment. Regional disparities are significant, with lower public resource allocations, and lower enrollment ratios in the three poorest regions. The quality of basic education in public schools remains poor, while it has steadily improved in private schools. Enrollments in higher levels are lagging behind those in basic education. Ghana ranks high among West African countries in health indicators, although its health expenditures tend to favor the non-poor. While more of the rural population have gained access to health services in recent years, many still have limited access, or none. Moreover, there is no link between the pattern of public expenditures - especially the pattern of immunization across Ghana - and health outcomes. To ensure that social services are efficiently, and equitably delivered in a fiscally constrained economy, the authors argue, public expenditures need to be linked to outcomes.